Faktor-Faktor yang Berhubungan dengan Pernikahan Dini di Desa Kebon IX Kecamatan Sungai Gelam Muaro Jambi Tahun 2022 - Diana Wulandari; Dwi Haryanti (Universitas Baiturrahim, 2023)
Early marriage is a marriage under the age that should not be ready for marriage. The age limit for marriage is 20 years for women and 25 years for men. The purpose of this study was to determine the factors associated with early marriage in Kebon IX village, Muaro Jambi. This research is an analytic research type with a cross sectional design which in this study studies the relationship between risk factors and disease (effect), observations or measurements of the independent variable (risk factor) and dependent variable (effect) are carried out once and at the same time. The variables studied were knowledge, parental income level, education and parental belief in early marriage, population 33 people, research sample 33 people. The source of data in this study is primary data, data obtained through questionnaires used by Bivariate and Univariate analysts. The results showed that there was a relationship between knowledge and early marriage (p-value = 0.000 0.05), parents' income level (p-value = 0.001 0.05), education level (p-value = 0.000 0, 05), and the level of parental confidence (p-value = 0.003 0.05).